Možnosti za znižanje temperature toplotnega vira z absorpcijskimi hladilnimi napravami - Remec, Janko (Strojniški vestnik, 2000)
The increasing importance of the simultaneous production of electricity, heat and cold results in increasingly rigorous demands on absorption chillers. These devices should be smaller, having a low cooling capacity and they have to be able to use low-temperature heating water at 90°C or below.As a result ,changes in generator construction are needed. Falling-film generators allow the use of hot water with lower temperatures. This type of generator avoids the need for high hydrostatic pressure, requires lower superheating and diminishes solution mixsing. Consequently we can use hot water at a temperature 7°C lower and reach the same cooling capacity.
Keywords: generatorji; sloj padajoči; litijev bromid; prenos toplote; hlajenje; absorberji